Climate change and resource development impacts in watersheds: Insights from the Nechako River Basin, Canada. (2nd December 2016) - Picketts, Ian M.; Parkes, Margot W.; Déry, Stephen J.
Abstract : Few studies to date examine the cumulative effects of climate change and resource development on social‐ecological systems, such as watersheds. In partnership with a watershed alliance we endeavoured to understand the interplay of climate change and resource exploitation impacts in the Nechako River Basin, which drains an area of 52, 000 km 2 in northwestern Canada as part of the Fraser River Basin. Existing regional climatic studies show a clear warming trend over the last century and a projected mean temperature increase of ∼2°C for the 2050s. Watershed stakeholders determined that hydroelectric development and forestry activities interrelate particularly closely with climate impacts related to ecosystem function, water supply, and (resultantly) community well‐being. Mining and oil and gas development do not currently represent a high level of concern, but will become problematic with future resource exploitation or climatic changes. The process was effective in grounding specific, day‐to‐day realities of climate change. The results illustrate the importance and challenge of considering both impact sources in tandem, and should inform ongoing regional planning and monitoring efforts. A major barrier to performing this type of assessment with regional stakeholders is communicating, cross‐referencing, and visualizing the interrelationships between climate change and resource development, which are independently highly complex. Les changements climatiques et le développement des ressources dans les bassins versants : leçons tirées du bassin de la rivière Nechako, Canada: À ce jour, peu d'études se sont intéressées aux effets cumulatifs des changements climatiques et du développement des ressources sur les systèmes socio‐écologiques, tels que les bassins versants. Nous avons entrepris, en partenariat avec un regroupement d'organismes de bassin versant, de comprendre l'interaction entre les effets des changements climatiques et du développement des ressources sur le bassin de la rivière Nechako qui draine les eaux d'un territoire couvrant 52 000 km 2 et faisant partie du bassin de la rivière Fraser dans le nord‐ouest du Canada. Les études climatiques régionales réalisées à ce jour montrent une nette tendance au réchauffement au cours du siècle dernier et une augmentation de la température moyenne projetée de ∼ 2 °C à l'horizon 2050. Les parties prenantes du bassin versant ont établi que les activités de développement hydroélectrique et de foresterie sont intimement liées avec les effets du climat agissant sur la fonction écosystémique, l'approvisionnement en eau, et finalement le bien‐être communautaire. Les secteurs de l'extraction minière et de l'exploration pétrolière et gazière ne suscitent actuellement pas de fortes inquiétudes, bien qu'ils risquent de poser problème à l'avenir avec l'exploitation des ressources ou les changements climatiques. Le processus a permis d'identifier des réalités particulières liées aux changements climatiques. Les résultats font ressortir l'importance et le défi de tenir compte simultanément des deux sources d'effets. Ils sont également susceptibles d'éclairer les mesures prises en matière de planification régionale et de surveillance. Une difficulté de ce type d'évaluation faisant appel aux parties prenantes régionales est de communiquer, d'effectuer des recoupements, et d'identifier les liens réciproques entre les changements climatiques et le développement des ressources, lesquels sont déjà hautement complexes. Key Messages: It is important to explore the interrelationships between resource development and climate change impacts. Climate change impacts watersheds in many ways, including by affecting ecosystem health, water supply, food supply, and human health and well‐being. In the Nechako River Basin, hydroelectric development and forestry activities have particularly strong overlays with climate impacts related to water and forest ecosystems and, as a result, health and well‐being.